Non‐Thermal Plasma Assisted Fabrication of Ultrathin NiCoOx Nanosheets for High‐Performance Supercapacitor. Issue 11 (28th October 2022) - Gicha, Birhanu Bayissa; Tufa, Lemma Teshome; Goddati, Mahendra; Adhikari, Samir; Gwak, Juyong; Lee, Jaebeom
Abstract: Invited for this month's cover picture is the group of Jaebeom Lee from Chungnam National University. The cover picture shows exfoliation of bulk NiCoO x layered double hydroxides into few layers of ultrathin nanosheets using a non‐thermal Ar‐plasma exfoliation strategy to obtain a single layer of NiCoO x nanosheets with excellent supercapacitive properties owing to improvement on the accessible active sites for charge storage and transport. Read the full text of the Research Article at 10.1002/batt.202200270 . Abstract : "This Front Cover illustrates exfoliation of bulk NiCoOx layered double hydroxides into few layers of ultrathin nanosheets using a non‐thermal Ar‐plasma exfoliation strategy to obtain a single layer of NiCoOx nanosheets with excellent supercapacitive properties owing to improvement on the accessible active site for charge storage and transport…" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Research Article on 10.1002/batt.202200270 .